ANALISIS PERBANDINGAN ELEMEN-ELEMEN BRAND EQUITY PADA PRODUK OBAT MAAG MEREK PROMAG DAN MEREK MYLANTA - Bernard E Silaban; Arini Arini (ESENSI: Jurnal Manajemen Bisnis, 2010)
Brand building is one importance aspect of marketing management. The brand itself can be based on the name of a company or the name of a product it produced. This research tries to compare the brand equity between two medical’s products, those are Promag and Mylanta. The result of research shows that based perceived quality and brand loyalty Mylanta is better than Promag.Keywords: brand awareness, brand association, perceived quality, brand loyalty, brand equity.